Caracterização dos agricultores agroecológicos de Itapipoca, no Ceará - Rocha, Thales Vieira (2023)
The municipality of Itapipoca has the three major environments of Ceará: mountain, semiarid plain, and coastal terraces, representing a microcosm of the state. In this same region, there is a long history of ethnic groups and peasant movements, with successful struggles for access to land. The agro-ecological knowledge and practices stand out as the source of many initiatives that have subsequently spread all over the state. Based on this contexto, the aim of this research was to study in socioeconomic and productive terms the families of agroecological farmers of Itapipoca advised by the Center for Labor Studies and Worker's Assistance (CETRA), considering considering the historical and socio-environmental context. Therefore, a systemic approach was used to feed back strategies and actions for the development of sustainable agriculture and agrarian systems. The specific objectives were to describe the socio-economic and productive characteristics of the agro-ecosystems of these farmers; to analyze through descriptive statistics the set and subgroups of agro-ecological farmers according to their historically and ethnically constructed identities based on geographical location. In addition, cluster analysis was used to classify and identify differences and affinities among agroecological farmers. Given the various dimensions and variables of the agrarian system, it was necessary to use a similarity coefficient capable of dealing with mixed data. Gower's distance was used for cluster analysis. The results indicate that, in general, settled and indigenous farmers are more socially participative than family farmers. Furthermore, farmers from the coastal and mountainous regions of Itapipoca developed more activities and production processing than farmers from the semiarid plain. Farmers in the semiarid plain stand out as having greater access to cisterns and production insurance policies. These differences stem from the type of farmers and environments in Itapipoca. They point to different strategies for sustainable rural development. The results of this research can be of great value to social organisations in planning actions within the territory, taking into account the particularities of the farmers.